Relation of body mass index (BMI) with cardiovascular response to head up tilt in healthy subjects - Rimi, Sadia Afrin; Sultana, Shamima; Rezwana, Iffat; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2020)
Background: Tilt table test is used for the last few decades to detect cause in unexplained syncope. The response to tilting may vary physiologically with obesity. Objective: To assess the relationship of BMI to cardiovascular response to tilting. Methods: This experimental study was conducted from March 2019 to Feb 2020 on 90 healthy subjects with different BMI. Fifty one subjects of both gender with BMI 18.5-24.9 kg/m2 were included in the non-obese group and 39 subjects of both gender with BMI of 25-29.9 kg/m2 were included in overweight group and they were further subdivided into male and female. Head up tilting was done for 10 minutes at 600 by using a motorized tilt table. Systolic blood pressure (SBP), diastolic blood pressure (DBP) were recorded by an automatic sphygmomanometer. Heart rate (HR) and peripheral capillary oxygen saturation (SpO2) were measured by a pulse oximeter. For statistical analysis, Independent sample ‘t’ test, Pearson’s correlation test and Chi square tests were applied. Results: Significantly smaller rise of heart rate was observed in overweight males and greater fall of systolic blood pressure was observed in overweight females. Conclusion: This study concluded that over weight is associated with reduced orthostatic tolerance to head up tilt test in both genders. J Bangladesh Soc Physiol. 2020, June; 15(1): 6-10